A marker set for measuring the kinematics of the lumbar spine and thoracic spine during running: a technical note - Preece, S. J.; Bramah, C.; Mason, D. (Journal of Human Sport & Exercise, 2015)
A protocol for tracking the motion of the lumbar spine, which uses seven skin mounted markers, has been adopted in previous studies investigating running. However, this configuration of can be difficult to track with passive motion capture systems. This study therefore investigated whether a four-marker configuration could accurately reproduce the pose of the lumbar spine obtained using the seven-marker configuration. The study also investigated two methods of tracking the thorax. The first method consisted of markers attached to the sterum and the second used two markers placed bilaterally over the acromioclavicular joints and another on the posterior thoracic spine. Kinematic data was collect for n=15 male subjects and the pose, calculated using the different tracking configurations, compared for both the lumbar spine and thoracic spine. The results demonstrated a good match between two lumbar tracking marker sets. However, there was considerable difference between the two thoracic markers sets which was likely due to movement of the arms influencing the pose of the thorax. We therefore recommend the use of four makers to track the motion of the lumbar spine and a rigid plate, mounted at the top of the sternum, to track motion of the thoracic spine during running.